The Interplay between Demographics and Decision-Making Styles in Botswana’s Retail Sector - Oluranti Sangodoyin; Rina Makgosa (Contemporary Research in Business, Management and Economics Vol. 1, 2024)
This study aims to analyse the decision-making styles displayed by retail shoppers, specifically exploring the impact of gender, age, education, income, and marital status on these styles. The study targeted the urban populations of Gaborone and Francistown, which together account for 20% of Botswana’s overall population. It conducted a survey among individuals aged 18 to 64. The data collection process consisted of conducting intercept surveys in shopping malls, resulting in 894 participants providing responses. The analysis identified three distinct decision-making styles prevalent among retail shoppers in Botswana: time-energy conserving, perfectionism, and fashion-hedonistic consciousness. Individuals who conserved time energy were older males with lower educational attainment, whereas perfectionistic shoppers were younger, educated, and married females. The fashion-hedonistic consciousness style was frequently observed among middle-aged, married women. These findings emphasise the significance for retailers to understand the subtle aspects of demographic influences on consumer decision-making styles, enabling the creation of focused marketing strategies to sustain a competitive advantage in the market.